Exploring Upland Rice Intercropping in Oil Palm Plantations: A Qualitative Literature Review of Economic and Ecological Perspectives - Judijanto, Loso (Jambura Agribusiness Journal, 2024)
The underutilization of land in young oil palm plantations presents a major challenge to both productivity and sustainability in tropical agriculture. This article explores upland rice intercropping as a promising strategy to optimize land use during the immature phase of oil palm cultivation. This study performs a qualitative literature analysis to examine the economic and ecological aspects of upland rice intercropping within oil palm plantations. The research consolidates findings from more than 80 peer-reviewed articles and institutional reports, chosen for their topic significance and regional diversity. Intercropping provides revenue diversification and enhances food security. It enhances soil fertility, biodiversity, and climate resistance. Nonetheless, implementation is constrained by knowledge deficiencies and policy limitations. This review emphasizes key elements affecting adoption and underlines the practice's role in sustainable land management in tropical areas.